2020
DOI: 10.1080/24740527.2020.1724775
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement for the Prescription of Pain Medication at Discharge after Elective Adult Surgery

Abstract: This Consensus Statement provides recommendations on the prescription of pain medication at discharge from hospital for opioid-naïve adult patients who undergo elective surgery. It encourages health care providers (surgeons, anesthesiologists, nurses/nurse practitioners, pain teams, pharmacists, allied health professionals, and trainees) to (1) use nonopioid therapies and reduce the prescription of opioids so that fewer opioid pills are available for diversion and (2) educate patients and their families/caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 112 publications
(169 reference statements)
0
53
0
3
Order By: Relevance
“…54 However, the effect was not identified for low-dose NSAIDs (diclofenac <125 mg/ day, ketorolac 120 mg/day) taken for less than 2 weeks, which has been confirmed in additional studies. [55][56][57] Nonetheless, spine surgeons have erred on the side of caution and prefer to avoid NSAIDs postoperatively. 58 Additionally, within patients undergoing colorectal surgery, a meta-analysis (24 studies, n = 31,877) showed an increased risk for anastomotic leaks (OR 1.73, 95% CI 1.31 to 2.29) with the use of NSAIDs.…”
Section: Nonsteroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…54 However, the effect was not identified for low-dose NSAIDs (diclofenac <125 mg/ day, ketorolac 120 mg/day) taken for less than 2 weeks, which has been confirmed in additional studies. [55][56][57] Nonetheless, spine surgeons have erred on the side of caution and prefer to avoid NSAIDs postoperatively. 58 Additionally, within patients undergoing colorectal surgery, a meta-analysis (24 studies, n = 31,877) showed an increased risk for anastomotic leaks (OR 1.73, 95% CI 1.31 to 2.29) with the use of NSAIDs.…”
Section: Nonsteroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…Patients should be made aware that scheduled acetaminophen and NSAIDs are first line for the management of post surgical pain, with opioids only being added if there is a need for further analgesia. Standard opioid prescribing should be tailored to the expected functional recovery of each surgical intervention with part-fills used to avoid excessive left-over opioid medications [8]. Nonpharmacological coping strategies should be reinforced and information regarding the appropriate use, storage and disposal of remaining opioid medications (i.e.…”
Section: Acute Post Discharge Periodmentioning
confidence: 99%
“…Nonpharmacological coping strategies should be reinforced and information regarding the appropriate use, storage and disposal of remaining opioid medications (i.e. return to the pharmacy) should be provided [8]. A meta-analysis of 44 studies (13,068 patients) published in 2020 showed that 61% of opioids are left unused after surgery [12].…”
Section: Acute Post Discharge Periodmentioning
confidence: 99%
See 2 more Smart Citations